Patient and public involvement in patient safety research: a workshop to review patient information, minimise psychological risk and inform research. Issue 1 (December 2016) - Furniss, Dominic; Iacovides, Ioanna; Lyons, Imogen; Blandford, Ann; Franklin, Bryony
Plain English summary Patient safety is a growing research area. However, although patients and the public are increasingly involved in clinical research, there is little guidance on how best to involve patients in patient safety research. Here we focus on how patients can contribute to the design of patient safety research. We conducted a workshop with patients as part of a project exploring errors and safety in the delivery of intravenous medication (medication given via a vein). The workshop was designed to explore how best to engage with hospital inpatients about these issues, to generate research topics, and to inform researchers about patients' experiences. Nine patients participated, each of whom had previously received intravenous medication. Participants advised against using terms such as 'error'; they also advocated caution when using terms such as 'safety' when describing the study to patients as this may worry some who had not thought about these issues before. We received thorough and useful feedback on our patient information sheets to ensure they were clear and understandable to patients. Patients also shared rich experiences with us about their treatment, which emphasised the need to extend our research focus to include a wider range of factors affecting quality and safety. Abstract Background Patient safety has attracted increasing attention in recent years. This paper explores patients' contributions to informing patient safety research at an early stage, within a project on intravenous infusion errors. Currently, there is little or no guidance on how best to involve patients and the wider public in shaping patient safety research, and indeed, whether such efforts are worthwhile. Method We ran a 3-hour workshop involving nine patients with experience of intravenous therapy in the hospital setting. The first part explored patients' experiences of intravenous therapy. We derived research questions from the resulting discussion through qualitative analysis. In the second part, patients were asked for feedback on patient information sheets considering both content and clarity, and on two potential approaches to framing our patient information: one that focused on research on safety and error, the other on quality improvement. Results The workshop led to a thorough review of how we should engage with patients. Importantly, there was a clear steer away from terms such as 'error' and 'safety' that could worry patients. The experiences that patients revealed were also richer than we had anticipated, revealing different conceptions of how patients related to their treatment and care, their role in safety and use of medical devices, the different levels of information they preferred, and broader factors impacting perceptions of their care. Conclusion Involving patients at an early stage in patient safety research can be of great value. Our workshop highlighted sensitivities around potentially worrying patients about risks that they might not have considered previously, and how to address these. Patient representatives also emphasised a need to expand the focus of patient safety research beyond clinicians and error, to include factors affecting perceptions of quality and safety for patients more broadly.